Bifunctional NiFe layered double hydroxide@Ni3S2 heterostructure as efficient electrocatalyst for overall water splitting. (18th September 2019) - Liang, Xinqi; Li, Yahao; Fan, He; Deng, Shengjue; Zhao, Xingyu; Chen, Minghua; Pan, Guoxiang; Xiong, Qinqin; Xia, Xinhui
Abstract: The tailored construction of non-noble metal bifunctional electrocatalysts for high-efficiency oxygen/hydrogen evolution reactions (OER/HER) is vital for the development of electrochemical energy conversion. Herein, we report a powerful combined wet chemical method to fabricate a novel binder-free NiFe layered double hydroxide@Ni3 S2 (NiFe LDH@Ni3 S2 ) heterostructure as an efficient bifunctional electrocatalyst for overall water splitting. The hydrothermal-synthesized NiFe LDH nanosheets are uniformly coated on the Ni3 S2 nanosheet skeleton forming 3D porous heterostructure arrays. By virtue of its synergistic advantages, including its binder-free characteristics, increased catalysis sites and structural stability, the as-obtained NiFe LDH@Ni3 S2 /NF electrode exhibits low overpotentials of 184 and 271 mV at 20 mA cm −2 for HER and OER in 1 M KOH, respectively. Notably, a low operation potential of 1.74 V at a current density of 20 mA cm −2 is achieved for overall water splitting with a stable cycling life. In addition, the intimate composite structure and sensitive interface of NiFe LDH@Ni3 S2 are responsible for the good electrocatalytic activity with a low Tafel slope, fast reaction kinetics and high stability. The versatile fabrication protocol and heterostructure interface engineering provide a new way to construct other bifunctional and cost-effective electrocatalysts for electrocatalysis.